Population genomic analysis reveals the emergence of high-risk carbapenem-resistant Escherichia coli among ICU patients in China. Issue 4 (April 2023) - Zhang, Rong; Li, Yan; Chen, Jiawei; Liu, Congcong; Sun, Qiaoling; Shu, Lingbin; Chen, Gongxiang; Wang, Zhiqiang; Wang, Shaolin; Li, Ruichao
Summary: Objectives: The increasing incidence of carbapenem-resistant Enterobacterales (CRE) mediated nosocomial infections has caused a significant public health burden globally. Currently, the prevalence and genomic characteristics of carbapenem-resistant Escherichia coli (CREC) in patients admitted to the intensive care unit (ICU) are unknown. Methods: Herein, we present a nationwide genomic investigation of CREC isolates among ICU patients in China in 2018 and 2020. In total, 113 CREC isolates were identified from 1105 samples in 25 hospitals, and investigated with phenotyping and genomics approaches. Results: Carbapenemases were produced in 94.69% (107/113) of CREC isolates, which comprise KPC-2 (n = 53, 49.53%), NDM (n = 51, 47.66%), IMP-4 (n = 2, 1.87%), and OXA-181 (n = 1, 0.93%). Notably, CREC isolates co-carrying mcr-9 and bla NDM-5 or tet (X4) and bla NDM-5 were first identified in clinical settings. The carbapenemase genes of most isolates were located on the plasmids. The bla KPC gene was mainly mediated by IncFII plasmids (n = 37, 69.81%), and bla NDM was located on the IncX3 plasmid (n = 36, 70.59%). CREC isolates belonged to diverse sequence types (STs) of which ST131 was the most prevalent bla KPC -positive CREC isolates (34/113, 30.09%), while bla NDM was associated with ST617 and ST410 isolates, thereby indicating that multiple CREC clones spread in Chinese ICU patients. Conclusions: This study highlights the emerging threat of high-risk CREC isolates such as ST131 circulating in the ICU in China. Hence, stringent monitoring of such high-risk clones should be performed.